TYPOLOGICAL STUDY OF HEROISM IN FANTASTIC WORKS (ON THE EXAMPLE OF R. BRADBURY AND H. SHAYKHOV WORKS) - Elmurodov Yusuf Kenjayevich (Scientific Impulse, 2023)
This article deals with the literary criticism and the problem of artistic psychology, the artistic creativity of human being in artistic works, the author's skill in illumination of human emotional experiences, the importance of studying works of an art in the aspect of comparative literature, as well as the role of heroic psychology in the work of American fantasy writer Ray Bradbury and Uzbek fiction Hojiakbar Shaykhov, common and distinctive properties were investigated in this research work.